Effects of ulū al-albāb on strategies practiced by companies for sustainable competitive advantage - Mhd. Sarif, Suhaimi (IIUM Press, International Islamic University Malaysia, 2020)
This study postulates that strategies with ulū al-albāb enabled companies to sustain competitive advantage. Profit maximisation and cost minimisation are common objectives for business entities. The study of management policy and corporate strategy has incorporated this element, but that is the only driving force to sustain competitive advantage and sustainable development. This study explores the effects of ulū al-albāb in the strategies practiced by companies for sustainable competitive advantage. The study found that the effects of ulū al-albāb are in the knowledge management for organisational learning to sustain talents, preservation of assets, and humanised approach in business networking.